Celiac disease in non-clinical populations of Japan - Fukunaga, Mai; Ishimura, Norihisa; Fukuyama, Chika; Izumi, Daisuke; Ishikawa, Nahoko; Araki, Asuka; Oka, Akihiko; Mishiro, Tomoko; Ishihara, Shunji; Maruyama, Riruke; Adachi, Kyoichi; Kinoshita, Yoshikazu (Journal of gastroenterology, 2018)
Background Celiac disease is a chronic autoimmune enteropathy caused by gluten ingestion. While its prevalence in Western countries is reported to be as high as 1%, the prevalence has not been evaluated in a large-scale study of a Japanese population. The aim of our study was to clarify the possible presence of celiac disease in a Japanese non-clinical population as well as in patients showing symptoms suggestive of the disease. Methods Serum samples were collected from 2008 non-clinical adults and 47 patients with chronic unexplained abdominal symptoms between April 2014 and June 2016. The anti-tissue transglutaminase (TTG) immunoglobulin A antibody titer was determined as a screening test for celiac disease in all subjects, and individuals with a value of >2 U/mL subsequently underwent testing for the presence of serum endomysial IgA antibody (EMA) as confirmation. Those testing positive for EMA or with a high concentration (>10 U/mL) of TTG were further investigated by histopathological examinations of duodenal mucosal biopsy specimens and HLA typing tests. Results Of the 2008 non-clinical adults from whom serum samples were collected, 161 tested positive for TTG, and all tested negative for EMA. Four subjects who had a high TTG titer were invited to undergo confirmatory testing, and the histopathological results confirmed the presence of celiac disease in only a single case (0.05%). Of the 47 symptomatic patients, one (2.1%) was found to have a high TTG titer and was diagnosed with celiac disease based on duodenal histopathological findings. Conclusion The presence of celiac disease in a non-clinical Japanese population was low at 0.05% and was rarely found in patients with unexplained chronic abdominal symptoms.